PENDEKATAN TEKNOLOGISDALAM MELAKUKAN REKAYASA PENGEMBANGAN INSTITUSI PERGURUAN TINGGI ISLAM - Subhan, Moh (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2016)
That in choosing educational institutions are selective and kompentabel let that happen in the community as keprofessionalan in managing and running an educational institution institutions in a new paradigm of management education. Implementing and education practitioners are tough and porposional. Just as teachers and lecturers who will thus understand their duties and roles is complete and comprehensive. Not just knowledge transfer (transfer of knowledge), but more than that, the task of educators is broader in scope, that is related to the duties of the profession, humanitarian, and social. In addition as a manager class also demonstrator, mediator and facilitator, evusaluator, and transfarmator or agent of change. In addition, managers of educational institutions should have clear philosophical achievement goals (vision and mission). Schools that do not have the vision and mission of mature and obviously tend origin and komirsil usal random. Like a ship, sailing on the ocean but did not have the destination. What will happen, obviously will oscillate, even impossible potential it will die in the hands of the school. Java people call this type as "sekloah waton" waton melaku, waton muride ono, ono waton lan duite. (Home run, his home there, and if there's money).